THE ROLES OF MUSIC IN RELEASING STRESS DURING COVID-19 LOCKDOWN IN VIETNAM: CASE OF VIETNAMESE YOUTH (Proceedings of the World Conference on Media and Mass Communication, 2023)
When COVID-19 causes a lot of problems for people and society. College students experience varying difficulties and degrees of stress, and this period had a significant negative impact on their mental health. One of the best ways for students to reduce stress during confinement is through music. This study aims to examine how students assess their stress levels during COVID-19 and explores how they choose their music genre as well as cope with their stress problems. Online surveys using simple question formats are conducted. Participants are students of Ho Chi Minh City's FPT University and experienced the COVID-19 period in Vietnam. Both quantitative and qualitative methodologies were used to analyse the data. SPSS program were used to count, calculate the data recorded from the survey. The findings show that academic overload stress, isolation stress, and fear of contagion stress were three main stressors. The most of respondents’ experiences on the epidemic is very modest level of stress. The result shows that FPT students tend to listen to music when they are facing academic stress and find it really effective to increasing mood and have mentally recovered while they find that music is not quite effective to release other 2 type of stress. Pop and Ballad were the two most popular genres listened by FPT students to reduce stress during the lockdown.
Keywords: COVID - 19, psychological , music, stress, university students